Performance-Based Budgeting Review from Local Government Budget: West Sumatra in 2017-2018 - Dyah Mutiarin; Aqil Teguh Fathani; Sakir Sakir; Muhammad Eko Atmojo (Universitas Muhammadiyah Yogyakarta, 2020)
The purpose of this article is to analyze the impact of the implementation of Spending Review using Performance-Based Budgeting (PBB) on the APBD (Regional Budget Revenues and Expenditures) of West Sumatra province the year 2018. This article uses the qualitative method to identify and interpret the Spending Review context that needs to be thoroughly identified. The result data were drawing through data codification, data presentation, and the result of data research. This research showed that the condition of the West Sumatra province's regional spending budget for the year 2018 was increasing. However, judging from the indirect expenditures budget of West Sumatra province was declining. Further, on the review of allocation result that has been done against the realization of regional expenditures budget, there were budget savings from the year 2017 – 2018. Then for indicator and performance review through health and education services showed an increased value of human development. Further on, the need deviation analysis showed that within two years of the government budget of West Sumatra province, i.e., the year 2017-2018, it has the rate level of need deviation with the allocation of spending budget 15.56%.